Serum anion gap and its interaction with diabetes in predicting mortality among critically ill patients with non-traumatic intracerebral hemorrhage - Yong Wen; Xiaorui Xie; Keli He (European Journal of Medical Research)
Abstract Background Non-traumatic intracerebral hemorrhage (ICH) is a significant cause of mortality and disability. The search for reliable prognostic markers to assess the risk of mortality in non-traumatic ICH patients is imperative. This study aimed to investigate the association between serum anion gap (AG) and mortality in critically ill patients with non-traumatic ICH. Methods We conducted a retrospective cohort study of patients with non-traumatic ICH from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database. Baseline characteristics were analyzed and stratified by AG quartiles. Univariate and multivariate Cox regression analyses were performed to assess the effect of AG on 28-day and 180-day mortality. Kaplan–Meier survival curves and restricted cubic spline analysis explored the relationship between AG quartiles and mortality and potential non-linear relationships, respectively. In addition, we tested for incremental effects of AG. Finally, we performed subgroup analyses to identify patient characteristics that may modify the relationship between AG and mortality. Results A total of 1,619 patients with non-traumatic ICH were enrolled in this study, with a mean age of 68.11 years, of them, 886 were males (54.73%). Cox regression analysis showed a significant association between AG and mortality, with each one-unit increase in AG increasing the risk of 28-day mortality by 8% and 180-day mortality by 6% in fully adjusted models. Kaplan–Meier analysis showed that the higher the AG quartile, the lower the probability of survival. Restricted cubic spline analysis showed a significant linear relationship between AG and risk of death. In addition, AG significantly improved the predictive performance of the base model for mortality in patients with non-traumatic ICH. Finally, subgroup analyses identified diabetes as a factor that significantly modified the relationship between AG and mortality in patients with non-traumatic ICH. Conclusions The study demonstrates the prognostic value of AG in non-traumatic ICH, especially in diabetic patients. Future prospective studies are warranted to validate these findings.